Vitamin D Loaded Carbon Nanofiber Aerogel Carriers and their Anticancer Activity Against Colon Cancer Cells - ÇALIŞKAN SALİHİ, ELİF; BİNGÖL ÖZAKPINAR, ÖZLEM (My University, 2022)
Transport of the drug to the tissue or cell is the key parameter for the treatment of many diseases, especially cancer. Carbon- based nanomaterials are excellent candidates as they have high chemical resistance ability, efficient mechanical properties and weightless characters (1). In recent years, literature data supports the role of vitamin D (VD) in cancer prevention and treatment. Many scientific articles have reported that VD has an important role in the onset, progression, prognosis and treatment of cancer (2,3). Aerogels, on the other hand, stand out with their much larger surface areas and ultra-porous structures compared to other nanomaterials which are important advantages for drug loading capacity (4,5). Developing highly biocompatible and economically inexpensive VD carrier systems were aimed in this study by using carbon Nanofibers in aerogel matrix as carrier materials due to the reasons such as the environmentally friendly, high biocompatibility, absence of cytotoxic effects and easy to handle production protocols. MTT method was used to determine the antiproliferative and cytotoxic activity of the prepared aerogels. In order to determine the effect of VD-loaded aerogels on the migration of colon cancer cells, wound dehiscence experiment was performed. Biochemical and morphological methods were used to investigate the possible apoptotic mechanism in colon cancer cells. As a result of MTT analysis, it was determined that the aerogel composite drug delivery system containing VD loaded active carbon Nanofibers did not have any cytotoxicity on normal cells, but had a cytotoxic and apoptotic effect on cancer cells. In addition, it was determined that the produced carrier system had an inhibitory effect on cell migration. It is thought that the aerogel containing VD-loaded carbon Nanofibers is effective on colon cancer and a promising new drug delivery system.
Keywords: Vitamin D; drug delivery system; carbon nanofibers; colon cancer